A metaheuristic for evaluation of an integrated special transport service. Issue 3 (2nd July 2020) - Posada, M.; Häll, C. H.
ABSTRACT: This work concerns evaluation of integrated demand responsive services, in which certain parts of the passengers' door-to-door journeys are served by fixed route public transport. The purpose of combining a special transport service with a fixed route service is to reduce the high, publicly subsidized, operational costs of the special transport service. To be able to recommend in which situations, or areas, it is beneficial to use an integrated service we present a metaheuristic for solving the routing problem in such a service. The metaheuristic can be implemented as part of an evaluation tool for policy makers and officials, providing insights into the effects of an integrated demand responsive service compared to a non-integrated. The metaheuristic is based on the adaptive large neighbourhood search (ALNS) framework. It is applied to a data set from a real-world, rural, demand responsive special transport service and the fixed route service available in the area. The objective used in our heuristic is to minimize the distance driven by the demand responsive vehicles. The distance driven is strongly related to the operational cost of the service. Our tests show that the distance driven by the demand responsive vehicles is reduced by 16%, giving a substantial cost reduction for the special transport service in the given area. Highlights Evaluation of integrated demand responsive service Combining special transport with a fixed route service to reduce operational costs Metaheuristic, based on the adaptive large neighbourhood search (ALNS) framework Comparing integrated service to non-integrated